Impact of front line demonstration on yield and economics of sunflower (Helianthus annuus L.) in Bihar: Impact of front line demonstration on yield and economics of sunflower (Helianthus annuus L.) in Bihar - VIKRAM BHARATI; U K SINGH; KAUSHAL KISHOR; C S CHOUDHARY (Journal of Oilseeds Research, 2020)
The frontline demonstrations were carried out in 102 farmer fields to demonstrate the impact of improved technology on yield of sunflower during the Spring, 2017. Each frontline demonstration was laid out on 1 acre area, and its adjacent one acre was considered as control (farmer’s practice). The frontline demonstration comprised of two hybrids namely, KBSH-44 and KBSH-53. KBSH-53 gave higher yield than KBSH-44. The result indicated that productivity of sunflower gained under improved demonstrated technology (17.10 q/ha) was higher as compared to farmer’s practices (13.14 q/ha). The study showed that improved technology gave 30.15% higher grain yield over farmers’ practices.